Melacak Kedalaman Tasawuf Modern Hamka di Tengah Arus Modernitas - Fahrudin F Fahru (JURNAL PENELITIAN KEISLAMAN, 2020)
This article aims to analyze the concept of modern Sufism (wasathiyah) thinking of Hamka. This paper uses the literature method by exploring and collecting various references such as books, articles, journals, and other documents relating to the themes discussed. The findings of this study are that Hamka is an archipelago Muslim intellectual figure known for his scientific productivity, evidenced by various works produced in various scientific disciplines, including modern Sufism. Modern Sufism was conceived by Hamka as a concept and movement to integrate the interests of the world and the hereafter, the world is used as a medium to draw closer to Allah. This moderate concept (tawasuth) will later produce a paradigm of a balanced modern society (tawazun), proportional (i'tidal), and tolerance (tasamuh), so that it becomes a socially and spiritually pious society.